The assumption of the duty crime’s theory and its consequences in Peruvian jurisprudence - Pariona Arana, Raúl (2023)
The theory of duty crime has been taken by national and international literature and their propositions have been applied by Peruvian jurisprudence. The usefulness of the theory has been identified mainly in public official’s crimes. In the case-law review, there isn’t a single theoretical position, because different approaches are taken place. However, it highlights the consensus about practical consequences that theory brings, such as the restriction of perpetration to people specially bound by a special duty, the consideration of the extraneus as participant and, about the evidentiary point of view, the necessity to prove the special duty and its infringement to determinate the perpetration in these crimes.